2021
DOI: 10.1016/j.jval.2020.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Direct Medical Costs of Advanced Breast Cancer Treatment: A Real-World Study in the Southeast of The Netherlands

Abstract: categories and the lifetime costs per patient, adjusted for censoring using Lin's method. The relationship between patients' characteristics and costs was studied using multivariable regression. Results: The average (SE) lifetime hospital costs of patients with advanced breast cancer were V52 709 (405). Costs differed considerably between patient subgroups, ranging from V29 803 for patients with a triple-negative subtype to V92 272 for patients with hormone receptor positive and human epidermal growth factor r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The 10-year Medicare cost (2007–2016) of treating stage I BC was USD 136,428 and that for stage IV was USD 376,563, with cost being exponentially related to stage [ 56 ]. A 2021 micro-costing Netherlands model for lifetime hospital costs for advanced BC found an average cost of € 52,709 (C$ 77,482) ranging from € 29,803 (C$ 43,810) in TN to € 92,272 (C$ 135,639) in HR+/HER2+ BC [ 57 ]. A 2022 US time-based ABC did not present integrated case costs by treatment possibility, stage and subtype, but derived similar costs [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 10-year Medicare cost (2007–2016) of treating stage I BC was USD 136,428 and that for stage IV was USD 376,563, with cost being exponentially related to stage [ 56 ]. A 2021 micro-costing Netherlands model for lifetime hospital costs for advanced BC found an average cost of € 52,709 (C$ 77,482) ranging from € 29,803 (C$ 43,810) in TN to € 92,272 (C$ 135,639) in HR+/HER2+ BC [ 57 ]. A 2022 US time-based ABC did not present integrated case costs by treatment possibility, stage and subtype, but derived similar costs [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that 2-[ 18 F]FDG-PET/CT was a cost-effective modality in the Netherlands and US, but not in the UK due to varying costs of services and different healthcare policies 28 . The average lifetime hospital-based costs of patients with advanced breast cancer was reported to be around €53,000 in the Netherlands 29 . The Dutch Council for Public Health and Health Care has set an informal ceiling ratio of €80,000 per gained extra year of survival for cancer patients, which could grant the use of 2-[ 18 F]FDG-PET/CT for response monitoring of MBC patients 10 , 30 .…”
Section: Discussionmentioning
confidence: 99%